E-Lecture online system / Lee Boon Keong - Lee, Boon Keong (2003)
In these early years of 21st century, information technology is playing an important role in our lives. With the explosion of knowledge and information nowadays, Information Technology must be adopted ot better manage of these aspect especially to increase the quality of teaching and learning, And this is why E-Lecture Online System (ELONS) comes in to bring a better experience in lecturing. Basically, ELONS is an online system that give better communication between lecturer and students and to make the teaching and learning process more effective. ELONS enable students to get their study material easily. ELONS also provide a center for students to exchange ideas and get help from course mates and lecturer easily and effectively. Students can check their exam result from their hometown at far. Students can read lecturer's announcement online and they get the result of their mid-semester test instantly! With ELONS, lecturers can give away their notes without much effort. Their announcements reach the student fast and effective. With the Forum in ELONS, lecturers get better understanding of their students level and progress. Lecturers will also be able to manage their student mailing list and contact certain group of student make possible. With the Online-test, lecturers do not have to mark the test paper anymore and a statistics report will be provided almost immediately. JavaServer Pages (JSP) is chosen to develop ELONS. This is to take advantage of the new JAVA J2EE technology for better technology investment. With ELONS, hopefully our country will have better quality of University graduates in the future.